The Effectiveness of Teaching Based on Visual Interpretive Thinking in Developing Aesthetic Awareness among Art Education Students - Hameed Mohsin, Malik ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
This study aims to identify the effectiveness of teaching based on visual interpretive thinking in developing aesthetic awareness among students of art education, in light of the challenges facing traditional teaching methods that focus on the formal description of artistic elements without delving into the interpretation of their aesthetic meanings. The study is based on the assumption that the artwork represents an open structure subject to interpretation, and that aesthetic meaning is formed through the interaction between the viewer and the artwork. This necessitates the adoption of instructional strategies that enable students to practice analysis, interpretation, and critique. The study adopted the experimental method using a design of two equivalent groups (experimental and control) with a pre-test and post-test application. The research sample consisted of (81) male and female students from the fourth year in the Department of Art Education, College of Fine Arts, University of Baghdad. The experimental group was taught according to the strategy of visual interpretive thinking, which is based on analyzing and interpreting artworks through dialogue, discussion, and visual contemplation, while the control group was taught using the traditional method. To achieve the objectives of the study, a scale of aesthetic awareness consisting of (40) items was constructed according to a five-point Likert scale. Its validity and reliability were verified using appropriate statistical methods. The results showed statistically significant differences between the two groups in favor of the experimental group in the post-test, indicating the effectiveness of teaching based on visual interpretive thinking in developing students’ aesthetic awareness. The results also revealed that this type of teaching contributes to activating higher-order cognitive processes, such as analysis, interpretation, and reconstruction of meaning, and enhances students’ emotional responses to the artwork, compared to traditional methods that are limited to direct reception. This is attributed to the fact that visual interpretive thinking allows students the opportunity to engage deeply with the artwork and to explore the underlying aesthetic relationships within it, which contributes to developing their abilities in artistic appreciation and critique. The study concludes that adopting teaching based on visual interpretive thinking represents an effective educational approach in developing aesthetic awareness among art education students, as it provides an interactive learning environment based on dialogue, contemplation, and meaning construction, in line with contemporary educational trends that emphasize the role of the learner as an active constructor of knowledge. DOI: https://doi.org/10.54633/2333-025-058-012